A study on the prevalence of risk factors associated with non-steroidal anti-inflammatory drugs-induced adverse effects among inpatients at a tertiary care hospital - J., Ashwini; X. C., Benisha; K., Hemalatha; B., Sangeetha (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used for pain relief and as antipyretics in day-to-day life. However, their adverse effects can be intensified in the presence of certain risk factors. This study aims to identify the risk factors associated with NSAID-induced adverse effects. It also serves to support clinical pharmacists in minimizing these risks and enhancing patient safety. Methods: Data from a total of 175 inpatients were collected prospectively using a structured data collection form based on defined inclusion and exclusion criteria. The study was conducted over a period of six months. The WHO-UMC causality assessment scale was used to evaluate adverse drug reactions (ADRs), and Hartwig’s severity assessment scale was used to determine the severity. SPSS software was employed for analysing the categorized data. Results: Among 175 patients receiving NSAID therapy, the most prevalent risk factor identified was polypharmacy (64%), followed by older age (38%). Preventive co-therapies, such as proton pump inhibitors (PPIs), were administered in 81.1% of cases. The study also reported a specific ADR generalized pruritus induced by diclofenac, which was assessed as probable on the WHO-UMC causality scale and mild (Level 2) on Hartwig’s severity scale. Conclusions: The study concludes that all NSAID prescriptions were rational and appropriate. Identifying risk factors and prescribing preventive co-therapies during NSAID treatment contributes to improved patient care and therapeutic outcomes.